MASYARAKAT PESANTREN DAN KARAKTERNYA SEBAGAI BENTUK MASYARAKAT MUSLIM IDEAL - Nasif, Hifni; 'Izzatul Amin, Maulida; Syahrozad Khunaifah (Pascasarjana Universitas Al-Qolam Malang, 2025)
Pesantren in Indonesia is not merely a place for religious education but also a center for character formation based on Islamic spirits such as sincerity, simplicity, independence, Islamic brotherhood, and freedom. These five pillars of philosophical soul then internalize into the connection of three principal structure; kiai, santri and masjid. This study employs a qualitative descriptive approach using literature review to examine the principles of pesantren life and how these principles contribute to the formation of the character of santri and the ideal Islamic society. After working this research, researcher can conclude that five pillars have significant role to form noble sosial life in pesantren. Sincerity serves as the foundation for harmonious relationships between the kiai and santri, fostering strong morality. Simplicity teaches santri to live in balance, fostering solidarity and sosial responsibility. Independence in pesantren prepares santri to manage their lives and contribute to the sustainability of the pesantren. Islamic brotherhood unites santri from diverse backgrounds, shaping them into agents of unity for the ummah. Pesantren also teaches freedom based on Islamic values, including freedom from physical and mental colonialism, while providing space for santri to plan their futures.